Detection of Lead (Pb) and Cadmium (Cd) Concentrations and Hazards in Some Baby Food Samples - Fadhel, Jabbar Faleh; Ghathwan, Maha (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This study was conducted to detect the concentration of lead and cadmium in baby foods, (18) samples were examined, which are the most available from various local markets in the city of Baghdad (at a rate of (9) samples of baby food consisting of cereals and (9) samples of baby foods consisting of vegetables). All samples were examined using an atomic flame absorptiometry (AAS-7000), all results showed the presence of lead and cadmium and the highest concentration value of lead in baby foods consisting of cereals (1.0986) and cadmium in baby foods consisting of vegetables (0.0015) ppm. Lead exceeded 100% limitations and cadmium did not exceed that. The results reported on the risks of contamination, as the mean daily intake (g/kg/d) for lead (1.3538) and cadmium amounted to (0.010), and the target hazard quotient index was high for the index (THQ>10) for lead in most of the samples examined and reached (THQ<10) in some samples examined, while cadmium all samples reached an index of (THQ<10). The study showed an increase in lead concentrations and perceptible risks and did not report an increase in cadmium concentrations outside the determinants, but it warns of imperceptible risks to the consumer. The study showed statistically significant differences between the levels of lead and cadmium and between the studied species and did not show statistically significant differences between the origins at the level of significance (0.05). It has been shown that these products pose a risk to children when consumed, so these products must be banned and ways must be found to reduce or prevent these pollutants with these products or find appropriate alternatives.